2012
DOI: 10.1016/s0140-6736(11)61621-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of paediatric pulmonary hypertension: a registry study

Abstract: Summary Background Paediatric pulmonary hypertension, is an important cause of morbidity and mortality, and is insufficiently characterised in children. The Tracking Outcomes and Practice in Pediatric Pulmonary Hypertension (TOPP) registry is a global, prospective study designed to provide information about demographics, treatment, and outcomes in paediatric pulmonary hypertension. Methods Consecutive patients aged 18 years or younger at diagnosis with pulmonary hypertension and increased pulmonary vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
349
4
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(405 citation statements)
references
References 26 publications
13
349
4
20
Order By: Relevance
“…Early evidence for the epidemiology of PH originated from adult registries; however, several newer pediatric international registries have contributed to our understanding of the disease in children as well. [1][2][3][4][5] Pediatric PH can be associated with a variety of underlying conditions, including congenital heart disease (CHD), connective-tissue disorders, pulmonary disease, and endocrine, metabolic, and infectious diseases such as HIV. PH is usually progressive from infancy to adulthood and associated with poor prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early evidence for the epidemiology of PH originated from adult registries; however, several newer pediatric international registries have contributed to our understanding of the disease in children as well. [1][2][3][4][5] Pediatric PH can be associated with a variety of underlying conditions, including congenital heart disease (CHD), connective-tissue disorders, pulmonary disease, and endocrine, metabolic, and infectious diseases such as HIV. PH is usually progressive from infancy to adulthood and associated with poor prognosis.…”
mentioning
confidence: 99%
“…An international registry showed that about 57% of children had iPH, a proportion similar to that observed in adults. 4,7 PH associated with CHD (PH-CHD) is more frequent in children (36%) than in adults (10%), 4 while other associated forms are uncommon in children. 8 For the initial assessment and follow-up of children with suspected or confirmed PH, transthoracic echocardiography (TTE) is the noninvasive diagnostic method of choice.…”
mentioning
confidence: 99%
“…The Tracking Outcomes and Practice in Paediatric Pulmonary Hypertension (TOPP) registry is a prospective registry that provides information on demographics, diagnostic evaluation, treatment and outcomes in paediatric pulmonary hypertension [25]. The recent TOPP analysis (31 centres in 19 countries; 2008-2010) identified important clinical features specific to the care of paediatric pulmonary hypertension, which drew attention to the need for paediatric data rather than extrapolation from adult studies [25]. In total, 317 of 362 pulmonary hypertension patients had PAH (PH Group 1, 88%), which was idiopathic or familial PAH in 182 (57%), and associated with other disorders in 135 (43%), of which 115 (85%) cases were associated with congenital heart disease.…”
mentioning
confidence: 99%
“…For example, brain natriuretic peptide (BNP) and N-terminal prohormone of BNP testing was performed in ,25% of children with pulmonary hypertension, and the 6-min walk test and cardiopulmonary exercise testing were conducted in only 38 and 7% patients, respectively. Both exercise tolerance tests are probably not reliable in children ,8 years of age and those with developmental delay, e.g., in trisomy 21 (13% in TOPP [25]). Hence, these functional variables do not serve well as (the sole) primary outcome in paediatric RCTs.…”
mentioning
confidence: 99%
“…Создаются системы для наследствен-ных болезней, при которых своевременно начатое лечение является залогом предупреждения развития тяжелых инвалидизирующих состояний. В качестве примеров можно представить следующие регистры: • этапного слежения за течением беременности [9]; • врожденных дефектов у новорожденных для обес-печения ранней интервенционной терапии [10]; • вакцинации и иммунизации [11]; • детей с отдельными заболеваниями или группами заболеваний (туберкулезом [12], сахарным диабе-том [13], легочной гипертензией [14], инфекцион-ными заболеваниями [15]); • детей с мукополисахаридозами I и II типов, полу-чающих патогенетическое лечение, и детей с ту-берозным склерозом, получающих современную терапию [16]; • младенческой и перинатальной смертности, обес-печивающий многофакторную оценку, включая анализ эпидемиологических факторов критиче-ского риска [17]. Федеральные российские системы обеспечивают вертикальную интеграцию медико-социальных дан-ных по уровням системы здравоохранения.…”
Section: регистры и мониторинг здоровья в электронном здравоохраненииunclassified